Cytotoxic xanthene derivatives from Homalium paniculiflorum. (March 2015) - Wu, Shou-Yuan; Fu, Yan-Hui; Chen, Guang-Ying; Li, Xiao-Bao; Zhou, Qi; Han, Chang-Ri; Song, Xiao-Ping; Du, Xiang-Jiao; Xie, Min-Li; Yao, Guo-Gui
Graphical abstract: Highlights: We investigated the constituents of the stems of Homalium paniculiflorum . Two novel xanthene derivatives were isolated from H. paniculiflorum . 11 known compounds were isolated from this plant for the first time. The growth inhibitory activities of new compounds1 and2 were measured in vitro . 1 and2 showed inhibitory effects with IC50 values comparable to those of cisplatin. Abstract: Two new xanthene derivatives, homapanicones A (1 ) and B (2 ), along with 11 known compounds (3 –13 ), were isolated from the stems of Homalium paniculiflorum . Among them, homapanicones A (1 ) and B (2 ) represent the first example of naturally occurring xanthene derivatives with an oxidized aromatic B unit, and the known compounds (3 –13 ) were isolated from this plant for the first time. These structures were established on the basis of extensive spectroscopic methods. Compounds1 and2 were tested for their cytotoxicities on HL-60, SMMC-7721, A-549, MCF-7, and SW480 human tumor cell lines. Homapanicones A (1 ) and B (2 ) showed cytotoxicities against various human cancer cell lines in the range of IC50 at 4.08–24.14 μM.